EFFECTIVENESS OF THE IMPLEMENTATION OF KAJANG BULUKUMBA INDIGENOUS PEOPLE’S INHERITANCE LAW - Egarianti Nuh; Syahruddin Nawi; Sukarno Aburaera (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal